Faculty Involvement in Translational Research and Interdisciplinary Collaboration at a US Academic Medical Center. (1st August 2010) - Weston, Christine M.; Bass, Eric B.; Ford, Daniel E.; Segal, Jodi B.
Abstract : Background: Forty-six academic health centers have been awarded Clinical and Translational Science Awards by the National Institutes of Health to enhance health by advancing translational research. Objective: As a recipient of a Clinical and Translational Science Award, we aimed to determine the prevalence of translational and interdisciplinary collaboration at our institution. Design, Setting, and Participants: We surveyed all full-time faculty and postdoctoral fellows (n = 3870) in the Johns Hopkins Schools of Medicine, Public Health, Nursing and Engineering, in late 2008. Main Outcome Measures: Outcomes included (1) the proportion of investigators involved in early (T1), late (T2), and reverse translational (RT) research; (2) barriers to translational research; (3) attitudes about translational research; (4) involvement in interdisciplinary collaboration; and (5) barriers to collaboration. Results: With 1800 respondents, the response rate was 55% for faculty and 40% for postdoctoral fellows. Of the 1314 investigators with more than 30% of their time committed to research, 69% reported conducting 1 or more types of translational research (T1 = 79%, T2 = 36%, RT = 36%). Attitudes about translational research revealed both concern and uncertainty. Fifty-four percent of respondents described translational research as having complex regulatory requirements; 42% felt that an individual's contributions suffer from underrecognition, 39% described it as high risk, and 35% consider funding less secure for translational researchers. Collaboration across school and types of research was common. Forty-seven percent of basic scientists collaborated with a clinical investigator in the last year, and 56% of clinical investigators collaborated with a basic scientist. Conclusions: Overall, investigators who did translational research reported a greater number of collaborators than those who did not.